When to Hold Them, When to Fold Them: Reassessing "Big Deals" in 2020. Issue 1 (19th May 2021) - Parang, Elizabeth; Whitt, Jeremy
ABSTRACT: While cancellations of "Big Deals" at research institutions are making the headlines, small- and medium-sized schools are also addressing the issue of managing their journal packages by cancelling or unbundling major publishers' journal packages. Although "Big Deals" were advantageous when first acquired, as the years passed, large publishers absorbed more publications annually, which brought higher costs and titles of lower relevance to the library. Each year librarians at Pepperdine University have analyzed cost per use, and each year the cost per use increased on many packages until these increases became unsustainable. Coinciding with this tipping point, alternatives to licensing entire packages emerged or became more viable. Libraries across the country realize that they no longer need to own everything. The authors go into details for each of the publishers' "Big Deals, " present reasons why they were cancelled or restructured, the alternative solutions implemented, and what the reaction has been.